Composição corporal e exigências nutricionais de cordeiros Santa Inês - Oliveira, Rangel dos Santos (2014)
There is little information on nutrient requirements for sheep raised in Brazil, so it is important to have more research in this area because a large number of publications is necessary for developing a table of Brazilian nutritional requirements for sheep. Thus, the present investigation was carried out to determine the body composition and protein and energy requirement for Santa Ines lambs. The experiment was conducted in the Department of Animal Science, Federal University of Sergipe. Twenty four no castrated Santa Ines lambs with an average age of three months and average live weight of 18.7 Kg, were randomly assigned to four treatments which were: corn silage; elephant grass silage + 15% of corn meal; area of sweet potato silage + 15% of corn meal; and robin + 15% corn meal, in a randomized block design. After an adaptation period of 14 days, an animal was randomly selected from each treatment and slaughtered to serve as reference for the estimates of empty body weight (EBW) and initial body composition of the remaining 20 lambs, totaling four treatments with five repetitions. The animals were slaughtered when they reached 30 kg live weight. Samples of blood, guts, organs, head, leather, legs, muscle, bone and fat from the left half carcass were collected to determine and estimate the amounts of nutrients in the EBW of the animals. The results were statistically analyzed using Proc Anova and Proc Reg using the statistical package SAS (2001). Regression analysis was made by the model y = a + b * X. The specific regression equations for each treatment did not differ (P < 0.01) by F test, so an overall regression equation for the EBW as a function of live weight was adopted, and the logarithm content of water, protein fat and energy in function of logarithm EBW lambs. The protein content of the empty body of the animals increased with increasing body weight, which is probably connected to the fact the animals are slaughtered aged solids that muscle development was still at a growing pace. The fat content in the empty body weight increased simultaneously with the increase of energy of body weight 15-30 kg, ranging from 57.88 to 243.10 g / kg EBW. The total net energy requirements of lambs rose with the increase in body weight from 15 to 35 kg, because when animals are in the final stages of growth occur with an increase in energy requirements with increasing body weight. The body content and requirements of protein and energy rose with increasing body weight of male sheep. Dietary protein and energy requirements are higher than those found in the NRC (2007).